2023
DOI: 10.1371/journal.pone.0281740
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of trematodes from the amphibian anomaly P hotspot: Role of planorbid snails

Abstract: Trematode infection of the second intermediate hosts can lead to changes in their fitness and, as a result, a change in the invasion rate of animal communities. It is especially pronounced during the invasion of parasite species that reduce activity due to the manipulation of hosts through the changes of their morphology and physiology. One of these cases is an anomaly P syndrome hotspot found in some populations of water frogs and toads in Europe caused by the trematode Strigea robusta metacercariae. The occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 119 publications
0
1
0
Order By: Relevance
“…In addition, laboratory experiments on Echinostoma (Rudolphi, 1809) (Echinostomatidae) have shown that this parasite can cause extensive mortality in tadpoles [68]. The P-syndrome hotspot found in tadpoles and metamorphs of water frogs and toads in Europe is due to parasitization by metacercariae of the trematode Strigea robusta (Szidat, 1928) (Strigeidae), which results in various deformities of the hindlimbs and forelimbs [69]. L. nigrovenosus metacercariae has been reported with a high prevalence (22.2%) in Pelophylax saharicus (Boulenger, 1913) in Morocco [37].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, laboratory experiments on Echinostoma (Rudolphi, 1809) (Echinostomatidae) have shown that this parasite can cause extensive mortality in tadpoles [68]. The P-syndrome hotspot found in tadpoles and metamorphs of water frogs and toads in Europe is due to parasitization by metacercariae of the trematode Strigea robusta (Szidat, 1928) (Strigeidae), which results in various deformities of the hindlimbs and forelimbs [69]. L. nigrovenosus metacercariae has been reported with a high prevalence (22.2%) in Pelophylax saharicus (Boulenger, 1913) in Morocco [37].…”
Section: Discussionmentioning
confidence: 99%